2014
DOI: 10.1128/aac.02636-13
|View full text |Cite
|
Sign up to set email alerts
|

Sheltering Effect and Indirect Pathogenesis of Carbapenem-Resistant Acinetobacter baumannii in Polymicrobial Infection

Abstract: The role of carbapenem-resistant Acinetobacter baumannii (CRAb) in polymicrobial infection remains elusive. Having observed the ability of CRAb to shelter other susceptible bacteria from carbapenem killing, we sought to determine the factors contributing to this sheltering effect by transforming different recombinant plasmids into recipient A. baumannii cells. The sheltering effects of CRAb were reproduced in recipient A. baumannii cells that highly expressed carbapenem-hydrolyzing class D ␤-lactamases (CHDLs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 36 publications
(46 reference statements)
1
48
0
Order By: Relevance
“…An acute pneumonia mouse model was used to evaluate in vivo competition between S. aureus and P. aeruginosa and showed that a P. aeruginosa wild-type strain outcompeted S. aureus, as calculated by the competition index, or the ratio of P. aeruginosa to S. aureus [110]. In a similar murine lung infection model, intratracheally co-inoculated carbapenem-resistant A. baumannii (CRAb) demonstrated synergy by protecting susceptible organisms, such as E. coli, against treatment with antibiotics [28].…”
Section: Lung Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…An acute pneumonia mouse model was used to evaluate in vivo competition between S. aureus and P. aeruginosa and showed that a P. aeruginosa wild-type strain outcompeted S. aureus, as calculated by the competition index, or the ratio of P. aeruginosa to S. aureus [110]. In a similar murine lung infection model, intratracheally co-inoculated carbapenem-resistant A. baumannii (CRAb) demonstrated synergy by protecting susceptible organisms, such as E. coli, against treatment with antibiotics [28].…”
Section: Lung Infectionmentioning
confidence: 99%
“…In biofilms and biofilm-related infections, these 'effects' include increased growth, antimicrobial tolerance, virulence and persistence, and enhanced production of exopolysaccharide (EPS) [17][18][19][20][21][22][23][24][25][26][27][28]. Another classic cooperative interaction is metabolic cross-feeding, or syntrophy, where one species makes a metabolic byproduct which enhances the growth of a neighbor [29].…”
Section: • Synergismmentioning
confidence: 99%
“…Liao et al reported that extracellular CHDL produced by Acinetobacter baumannii helped other susceptible bacteria to survive against the eradication of carbapenem and named this phenomenon the sheltering effect (31). This effect is strongly affected by a strong promoter of the CHDL gene.…”
mentioning
confidence: 99%
“…This indicate a greater importance for the presence of CRAB in clinical settings and emphasize the urgent need for more effective controls of CRAB in polymicrobial infection (Liao et al, 2014). …”
Section: Introductionmentioning
confidence: 99%